Insurers : Too Many, Too Few, Or "Just Right"? - Thorburn, Craig (The World Bank, 2008)
In many markets, industry and policymakers agree that there may be too many insurers. In others, the consensus is that there could be benefit from more competition. But this broad consensus is often supported by evidence that is more qualitative, anecdotal, or judgmental despite being unanimous. What is less clear, however, is how far consolidation or liberalization will go, how fast, and when it will end. This paper presents some initial observations from a cross-country data set and proposes that individual country results can be interpreted against this data set to inform expectations regarding trends in competition, concentration and consolidation, to inform analysis of the sector, for individual firm strategic planning and wider market risk assessments. A "natural level" for measures is suggested as a starting hypothesis. Further consideration is then made of the role of absolute market size, stage of market development, and differentials between life and non life segments. Analysis of the natural level, adjusted for market conditions, can then be used to develop preliminary views on current and expected market dynamics, strategic planning, and to inform policy, regulatory and supervisory priorities